Cytotoxic and apoptotic effects of ternary silver(i) complexes bearing 2-formylpyridine thiosemicarbazones and 1, 10-phenanthroline. Issue 16 (3rd April 2020) - Silva, Débora E. S.; Becceneri, Amanda B.; Solcia, Mariana C.; Santiago, João V. B.; Moreira, Mariete B.; Gomes Neto, José A.; Pavan, Fernando R.; Cominetti, Márcia R.; Pereira, José C. M.; Netto, Adelino V. G.
Abstract : Ag(i ) complexes induced apoptosis in triple negative breast cancer cells and were appreciably less cytotoxic against non-tumor cells. Abstract : New silver(i ) compounds containing 2-formylpyridine- N (4)- R -thiosemicarbazones and 1, 10-phenanthroline (phen) were synthesized and characterized by spectroscopic techniques (IR and NMR), elemental analysis, ESI-MS and molar conductance measurements. In these complexes, both phen and thiosemicarbazone ligands are coordinated in a chelating bidentate fashion. Compounds 1–3 not only showed good in vitro antiproliferative activity against human lung (A549) and breast tumor cells (MDA-MB-231 and MCF-7), with IC50 values ranging from 1.49 to 20.90 μM, but were also demonstrated to be less toxic towards human breast non-tumor cells (MCF-10A). Cellular uptake studies indicated that compounds 1–3 were taken up by the MDA-MB-231 cells in 6 hours. Cell death assays in the MDA-MB-231 cells were conducted with compound 1 aiming to evaluate its effects on cell morphology, induction of apoptosis, the cell cycle, reactive oxygen species (ROS) formation and mitochondrial membrane potential (Δ ψ m ). Compound 1 caused morphological changes, such as cell shrinkage and rounding, increased the sub-G1 phase population, and induced apoptotic cell death, ROS formation and loss of mitochondrial membrane potential (Δ ψ m ). DNA binding results revealed that 1 interacted with the ct-DNA minor groove. Complexes 1–3 also exhibited good in vitro activity against M. tuberculosis H37Rv, with MIC values ranging from 3.37 to 4.65 μM.